Two new species of Demonax (Sabellidae:Polychaeta) from Liverpool Bay - Knight-Jones, Phyllis; Walker, A.J.M. (Journal of Natural History, 1985)
Demonax cambrensis sp. nov. resembles the east Pacific Demonax medius (Bush), but is thinner though just as long and has less than 15 axial cells in a radiole cross section. Demonax torulis sp. nov. resembles Demonax japonicus (Moore) in having thoracic tori so small that they do not indent the ventral shields, but differs in having broad-hooded inferior thoracic setae. Both benefit by enrichment of the sediment with sewage sludge.
World Polychaeta Database (WPolyDb)